The CYP71AZ P450 Subfamily: A Driving Factor for the Diversification of Coumarin Biosynthesis in Apiaceous Plants - Krieger, Célia; Roselli, Sandro; Kellner-Thielmann, Sandra; Galati, Gianni; Schneider, Bernd; Grosjean, Jérémy; Olry, Alexandre; Ritchie, David; Matern, Ulrich; Bourgaud, Frédéric; Hehn, Alain (Frontiers in Plant Science, 2018)
The production of coumarins and furanocoumarins in higher plants is widely considered a model illustration of the adaption of plants to their environment. In this report, we show that the multiplication of cytochrome P450 variants within the CYP71AZ subfamily has contributed to the diversification of these molecules. Multiple copies of genes encoding this enzyme family are found in Apiaceae, and their phylogenetic analysis suggests that they have different functions within these plants. CYP71AZ1 from Ammi majus and CYP71AZ3, 4, and 6 from Pastinaca sativa were functionally characterized. While CYP71AZ3 merely hydroxylated esculetin, the other enzymes accepted both simple coumarins and furanocoumarins. Superimposing in silico models of these enzymes led to the identification of different conformations of three regions in the enzyme active site. These sequences were subsequently utilized to mutate CYP71AZ4 to resemble CYP71AZ3. The swapping of these regions lead to significantly modified substrate specificity. Simultaneous mutations of all three regions shifted the specificity of CYP71AZ4 to that of CYP71AZ3, exclusively accepting esculetin. This approach may explain the evolution of this cytochrome P450 family regarding the appearance of furanocoumarins in parsnip and possibly in the Apiaceae.